EFEKTIVITAS INFOGRAFIS SEBAGAI PENDUKUNG MATA PELAJARAN IPS PADA SISWA SISWI KELAS 5 SDN KEPATIHAN DI KABUPATEN BOJONEGORO - Susetyo, Hendri Rahman; Bahruddin, Muh; Windarti, Tantri (Jurnal Art Nouveau, 2015)
Abstract: This research aims to determine the effectiveness of infographics as supporting social sciences subjects for Kepatihan elementary school in Bojonegoro. This is a correlation research using survey methods and questionnaire. The population in this study are 5th students of Kepatihan Elementary School in Bojonegoro which amounts to 114 people. Whereas instruments used to research the effectiveness of this is infographics media, where this infographic created from the student handbook and converted into an infographics form. The results of test scores obtained from the method further infographics compared to the previous generation test scores by subject matter the same one. Then the data were analyzed using the methods of testing variable. Before the data is analyzed there should be testing requirements of data analysis ie hypothesis testing using regression analysis. After testing the hypothesis completed, the data collected from the questionnaires were processed and applied into the scale interpretation according Riduwan scores to measure the effectiveness/strength of infographics. Then the results obtained from testing the hypothesis in tolerance 0.05 methods of use of infographics (new method) is better than the old method. While testing the variables to get the value of infographics 79.23% (Approaching strong), color variable 78.13% (Approaching strong), letter variable 73.45% (Strong enough), and layouts variable 74.92% (strong enough). Â Keywords : effectiveness, infographics, Design, Social, Student, Elementary School